UVX 2008 - 9e Colloque Sur Les Sources Cohérentes Et Incohérentes UV, VUV Et X : Applications Et Développements Récents 2009
DOI: 10.1051/uvx/2009020
|View full text |Cite
|
Sign up to set email alerts
|

Optical and photonic material hardness for energetic environments

Abstract: Abstract.We studied the effects of dielectric change in the chemical composition and in the realization procedures under radiation exposure. We have compared the radiation effects on Ge-doped and F-doped fibers and preforms: the first play a crucial role in the photosensitivity property, the second improves the dielectric radiation hardness even at low concentrations. The use of different spectroscopic techniques (RIA, OA, EPR) allow the identification of the point defect formation mechanisms at the origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The broad band may originate from the P-related defects that are produced upon X-ray irradiation. Origlio et al 48 reported an emission center originating from the P-related point defect in amorphous silica; this center features a broad fluorescence band centered at 3.0 eV (413 nm) and a long lifetime (5−6 ms) upon 4.8 eV (258 nm) laser excitation. Unlike that in the report from Origlio et al, 48 using a 488 nm argon-ion laser as an excitation source, we observe a broad fluorescence band centered at 550 nm whose intensity increases with the increasing radiation dose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad band may originate from the P-related defects that are produced upon X-ray irradiation. Origlio et al 48 reported an emission center originating from the P-related point defect in amorphous silica; this center features a broad fluorescence band centered at 3.0 eV (413 nm) and a long lifetime (5−6 ms) upon 4.8 eV (258 nm) laser excitation. Unlike that in the report from Origlio et al, 48 using a 488 nm argon-ion laser as an excitation source, we observe a broad fluorescence band centered at 550 nm whose intensity increases with the increasing radiation dose.…”
Section: Methodsmentioning
confidence: 99%
“…Origlio et al 48 reported an emission center originating from the P-related point defect in amorphous silica; this center features a broad fluorescence band centered at 3.0 eV (413 nm) and a long lifetime (5−6 ms) upon 4.8 eV (258 nm) laser excitation. Unlike that in the report from Origlio et al, 48 using a 488 nm argon-ion laser as an excitation source, we observe a broad fluorescence band centered at 550 nm whose intensity increases with the increasing radiation dose. In addition, we can also observe this luminescence band upon 488 nm excitation from an 18 kGy X-ray-irradiated P single-doped (P/SiO 2 ) sample, as shown in the inset of Figure 7a.…”
Section: Methodsmentioning
confidence: 99%
“…Although formally the disordered hetero-structures do not have equivalent propagating states, an analogous phenomenon occurs[22]. applications requiring high and stable transmission in UV and visible spectral range[23]. Photons interact very weakly with transparent optical media.…”
mentioning
confidence: 99%